NEUROPHYSIOLOGICAL ANALYSIS AND MANAGEMENT OF THE HUMAN FUNCTIONAL STATE IN THE CLINIC AND AT WORK (TOWARDS THE 45th ANNIVERSARY OF THE ESTABLISHMENT OF THE APPLIED NEUROPHYSIOLOGY LABORATORY AT THE RESEARCH INSTITUTE FOR COMPLEX PROBLEMS OF HYGIENE AND OCCUPATIONAL DISEASES) - Флейшман, Арнольд Наумович (Medicine in Kuzbass, 2021)
The article considers fundamental and applied studies in the applied neurophysiology laboratory of the Research Institute for Complex Problems of Hygiene and Occupational Diseases for 45 years. The article highlights the evolution of the methodological approaches in scientific researches, the main publications, patents, scientific achievements, international relations as well as future prospects.
Keywords: neurophysiological analysis; applied neurophysiology laboratory; scientific achievements